Weak antilocalization effect in exfoliated black phosphorus revealed by temperature- and angle-dependent magnetoconductivity. (5th February 2018) - Hou, Zhipeng; Gong, Chen; Wang, Yue; Zhang, Qiang; Yang, Bingchao; Zhang, Hongwei; Liu, EnKe; Liu, Zhongyuan; Zeng, Zhongming; Wu, Guangheng; Wang, Wenhong; Zhang, Xi-xiang
Abstract: Recently, there have increasingly been debates on whether there exists a surface resonance state (SRS) in black phosphorus (BP), as suggested by recent angle-resolved photoemission spectroscopy results. To resolve this issue, we have performed temperature- and angle-dependent magnetoconductivity measurements on exfoliated, high-quality BP single crystals. A pronounced weak-antilocalization (WAL) effect was observed within a narrow temperature range of 8–16 K, with the electrical current flowing parallel to the cleaved ac -plane (along the a - or c -axis) and the magnetic field along the b -axis. The angle-dependent magnetoconductivity and the Hikami–Larkin–Nagaoka model-fitted results have revealed that the observed WAL effect shows surface-bulk coherent features, which supports the existence of SRS in BP.